Perbandingan Efektivitas Obat Kumur Kimia Dengan Obat Kumur Herbal Kombucha Bunga Telang Untuk Kesehatan Gigi dan Mulut - Ardana, Mellysa Putri; Nurbaeti, Nabila; Hanifah, Putri Dwi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Mouthwash is an aqueous concentration of antibacterial solution that is used for fighting oral microbes, fighting oral infections, cleansing, for eliminate fresh mouth odor and antiseptic. Mouthwash plays an important role in oral hygiene of an individual, mouthwash helps to alleviate the symptoms of gingivitis, inflamed gums and can also be relied upon to destroy bacterial pathogens. The purpose of this study was to determine the effectiveness of the use of chemical mouthwash and herbal mouthwash. chemical mouthwash and bay flower kombucha herbal mouthwash for oral health. and oral health. This research is a quantitative research with the method of comparative or comparison method. This checking process is carried out by gargling using clean water, then the water from the mouthwash is stored in a container to observe the bacteria contained in it. The use of chemical mouthwash and herbal kombucha bay flower will be effective depending on a person's dental or oral problems. Chemical mouthwash is more effective for people who experience bad breath problems because it can refresh the mouth. Meanwhile, bay flower kombucha herbal mouthwash is effective for overcoming toothache or infection problems that occur in a person. That occurs in a person. Mouthwash preparations made from solution gives an optimal effect in inhibiting the growth of Staphylococcus aureus bacteria. Growth of Staphylococcus aureus bacteria.